Towards an urban planners’ perspective on Smart City - Papa, Rocco; Gargiulo, Carmela; Galderisi, Adriana (TeMA - Journal of Land Use, Mobility and Environment, 2013)
The concept of “Smart City”, providing a solution for making cities more efficient and sustainable, has been quite popular in recent years, encouraging reflections, ideas, researches and projects for a “smart” urban development. A smart city is generally meant as a city capable of joining “competitiveness” and “sustainability”, by integrating different dimensions of development and addressing infrastructural investments able to support economic growth as well as the quality of life of communities, a more careful management of natural resources, a greater transparency and participation to decision-making processes. Based on those assumptions, this contribution tackle the controversial subject of Smart City, starting from the review of the scientific Italian and international literature that, from the Eighties to the Nineties, has been largely focused on ICTs and their impacts on urban development. Then, the focus shifts on the large debate on smart cities that has been developing from the beginning of 2000s and on the numerous institutional initiatives up to now implemented by the European Union for building up the Smart City. Finally, the article highlights how, despite these efforts, a shared definition of the term is still missing and current approaches to the issue are still very heterogeneous; it emphasizes, on the opposite, the key-role that urban planning, grounding on a holistic approach to cities’ development, should play in coordinating and integrating urban policies addressed to building up a Smart City.